Nitric oxide and malondialdehyde concentration in grastric contents and blood in an equine model of gastric ulcer induced by phenylbutazone - Zuluaga, Angélica M; Silveira A, Geraldo E; Martínez A, José R (Revista Colombiana de Ciencias Pecuarias, 2016)
mechanisms of gastric mucosal injury include cellular damage by oxygen free radicals, which can be indirectly measured through malondialdehyde (MDA). Production of nitric oxide (NO) maintains gastric tissue perfusion through vasodilatation. Objective: to demonstrate oxidative stress and impaired gastric perfusion measuring NO and MDA in gastric contents and blood of equines subjected to a gastrointestinal ulceration induction protocol. Methods: a gastrointestinal ulceration induction protocol involving fasting and oral administration of phenylbutazone was performed on five horses. NO and MDA were measured before and after protocol induction and presence of fecal occult blood (FOB) was evaluated. Animals underwent gastroscopy at the beginning and end of the protocol. Results: horses presented variability in hematological and FOB exams. Azotemia, hyperphosphatemia, and hypocalcemia were found in all animals. No significant changes were found in enzymatic activity. At the end of the protocol, 40% of the horses showed varying degrees of gastric ulceration. NO production in the stomach decreased by 60%, whereas MDA production increased by 55% after the protocol. Plasma concentration of MDA average increased 96 hours after starting the protocol. There were no significant differences in mean plasma NO during the protocol. Conclusion: the protocol used to induce gastric ulcers produces diminished cytoprotection (by NO) and induces oxidative stress in the gastric mucosa.